2018
DOI: 10.1111/aos.13938
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between corneal and retinal neurodegenerative changes and their association with microvascular perfusion in type II diabetes

Abstract: Purpose The pathophysiology of diabetic neurodegeneration and microvasculopathy remains controversial. Neurosensory layer thickness and corneal nerve fibre loss represent potential biomarkers of neuropathy. The purpose of this cross‐sectional study was to determine the correlation between these neurodegenerative features and their association with retinal microvascular integrity in patients with type II diabetes without retinopathy. Methods Nerve fibre length (NFL), density (NFD) and branch density (NBD) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Although we found reductions in both the RNFL and corneal nerve parameters independently, we and others (51) found no correlation between neural changes in the retina (central nervous system) and cornea (peripheral nervous system). At present, the reason for this finding is unclear.…”
Section: Discussioncontrasting
confidence: 92%
“…Although we found reductions in both the RNFL and corneal nerve parameters independently, we and others (51) found no correlation between neural changes in the retina (central nervous system) and cornea (peripheral nervous system). At present, the reason for this finding is unclear.…”
Section: Discussioncontrasting
confidence: 92%
“…Changes detected in this layer can be indicative of neurodegeneration and can potentially occur in patients with DM even before the development of DR. This may be due to damage from chronically elevated blood sugar levels [53][54][55]. A 3-year longitudinal study confirmed significantly faster rates of GC-IPL thinning in eyes that developed incident DR compared to those that remained non-DR, although both groups showed decreased thickness [56].…”
Section: Retinal Neurodegenerationmentioning
confidence: 87%
“…Apart from the GC-IPL, the peripapillary retinal nerve fiber layer (pRNFL) and macular retinal nerve fiber layer (mRNFL) are other important retinal structural parameters that need to be considered for early detection of DR [57][58][59][60]. More recently, Hafner et al reported a significant association between pRNFL but not mRNFL with parafoveal vessel density detected by OCTA [55]. This finding corroborated the result reported by the EU-ROCONDOR study, which demonstrated a strong correlation between narrower retinal arteriolar caliber and thinning of the pRNFL, reflecting the close relationship between microvascular abnormalities and neurodegeneration in the pathophysiology of diabetic retinopathy [61].…”
Section: Retinal Neurodegenerationmentioning
confidence: 99%
“…In this study, it was found that although there was no significant difference of CRT between preoperative and postoperative, the thickness of the paracentral fovea retina in all quadrants was significantly increased 3 months after surgery, and the thickness of the nasal paracentral retina was significantly increased 3 months after surgery compared with that before surgery. In addition, the blood flow density postoperative in superficial and deep nasal paracentral fovea retina was significantly lower than that before surgery, suggesting that the decrease of GCL-IPL complex may be an important reason for the blood flow density change in superficial and deep layers after surgery ( Hafner et al, 2019 ). At present, OCTA can only evaluate the retina of optic disk area within 4.5 mm × 4.5 mm.…”
Section: Discussionmentioning
confidence: 99%